Philip Morris international delivering a smoke-free future - are Sdgs the solution? a new playing field - Neves, Alice Guerra Barosa Jardim (2022)
The work project consists of a case study, teaching note and project evaluation report on Philip Morris International’s (PMI) mission of delivering a smoke-free future. The case study pre-sents the company’s transformation and introduces PMI’s next-generation product IQOS that is said to have the potential to be less harmful than conventional cigarettes. The evaluation report analyses and provides recommendations for PMI’s main challenges: widespread mistrust from stakeholders and lack of awareness for IQOS. This teaching note expands on the concepts of sustainability, the introduction of SDGs practices, impact measurement, and their relevance for such a transformation.